2019
DOI: 10.1039/c9ta05637h
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Co, Mn, Ni and Fe oxide co-catalysts on TiO2 for photocatalytic water splitting reactions

Abstract: Here we report a systematic study of Co, Mn, Ni and Fe oxides as co-catalysts for HER and OER that were prepared by wet impregnation of the corresponding metal acetylacetonate salts onto a model TiO2 substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 64 publications
16
48
0
Order By: Relevance
“…Photocatalytic water splitting implies a non-spontaneous process, where the light photons are used to break the water molecules assisted by a photocatalyst, which generates photoexcited charge carriers, i.e., e − /h + pairs, delivering them to the solid-liquid interface, where the redox half-reactions of water oxidation and reduction are catalyzed [110,111], analogously, as described above for photocatalytic water treatment. The difference in water splitting is that photogenerated charges (i.e., e − and h + ) need to react with H + as the electron acceptor adsorbed on the photocatalyst surface or within the surrounding electrical double layer of the charged particles in order to generate H 2 [112], instead of O 2 generating O 2…”
Section: Photocatalytic Water Splittingmentioning
confidence: 99%
“…Photocatalytic water splitting implies a non-spontaneous process, where the light photons are used to break the water molecules assisted by a photocatalyst, which generates photoexcited charge carriers, i.e., e − /h + pairs, delivering them to the solid-liquid interface, where the redox half-reactions of water oxidation and reduction are catalyzed [110,111], analogously, as described above for photocatalytic water treatment. The difference in water splitting is that photogenerated charges (i.e., e − and h + ) need to react with H + as the electron acceptor adsorbed on the photocatalyst surface or within the surrounding electrical double layer of the charged particles in order to generate H 2 [112], instead of O 2 generating O 2…”
Section: Photocatalytic Water Splittingmentioning
confidence: 99%
“…Figure 7 compares the obtained reaction rates and for all CoO x -TiO 2 films under visible and UV–Vis illumination. All films presented significant photocatalytic activity under visible light, confirming the positive effect of CoO x nanoclusters on titania’s VLA photocatalytic performance by surface states that enable visible-light activation and interfacial charge transfer that promotes charge separation and/or their cocatalyst action [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 23 ]. Distinct improvements of both reaction rates and were observed for the bilayer CoO x -P25/PC films surpassing the additive result of the constituent layers, indicating significant activity enhancement by the PC supported heterostructure.…”
Section: Resultsmentioning
confidence: 80%
“…Surface modification of TiO 2 by metal-oxide nanoscale clusters has emerged as a facile yet very efficient method for the development of visible-light-activated (VLA) photocatalysts for solar-driven applications including organic pollutant decomposition and water splitting [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Among wet impregnation routes of different metal salt precursors, chemisorption of the bulky metal acetylacetonate complexes on titania followed by post-thermal decomposition has been an effective approach for the dispersion and controlled loading of molecular-scale metal-oxide nanoclusters on TiO 2 [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As found by the HRTEM, small amount of impurities of cobalt and iron oxides were also formed at R w = 15. However, some researchers reported that cobalt oxides [ 36,37 ] and iron oxides [ 36 ] acted as cocatalysts for OER on TiO 2 . Therefore, it is not probable that the lower photocatalytic activity of CFCO/TiO 2 at R w = 15 was caused by the impurities.…”
Section: Resultsmentioning
confidence: 99%